The Efficacy and Safety of Diyushengbai Tablet on Preventing and Treating Leukopenia Caused by Radiotherapy and Chemotherapy Against Tumor: A Systematic Review and Meta-Analysis - Xu, Xiaoqing; Li, Hongmin; Hu, Xiwen; Liu, Juan; Zhao, Fang; Xie, Kaiyong; Wang, Jun (Frontiers in Pharmacology, 2022)
Background：Leukopenia is one of side effects of radiotherapy and chemotherapy. Diyushengbai tablet is used to prevent and treat leukopenia caused by various reasons. To systematically analyze the therapeutic effects of Diyushengbai tablet on preventing and treating leukopenia caused by radiotherapy and chemotherapy，a meta-analysis was performed. Objectives：This study aimed to systematically evaluate the efficacy and safety of Diyushengbai tablet for leukopenia caused by radiotherapy and chemotherapy. Methods：Data searching included PubMed, The Cochrane Library, China Knowledge Network (CNKI), China Biomedical Literature Database (CBM), Wanfang Data Knowledge Service Platform and VIP. The scanning reports deadline is until November of 2021. The bias risk evaluation criteria developed by the Cochrane collaborative organization were used to evaluate the literature quality of the included studies. The RevMan5.4 software was used to analyze the data, and the stataSE16.0 was used to perform the Egger test. Results：After selecting of all the database, a total of 41 reports which involved 3793 cases were analyzed. Meta-analysis showed that Diyushengbai tablet can significantly reduce the white blood cell suppression caused by radiotherapy and chemotherapy, improve the patient's white blood cell count and neutrophil count, compared with treatment of oral WBC elevating drugs such as Leucogen Tablets, Batilol Tablets or additional G-CSF ultilization.The results of Meta analysis showed that for preventive medication purpose, the overall incidence of leukocyte suppression was [RR=0.74, 95%CI (0.59, 0.92), P=0.006], and the white blood cell count was [MD=1.12, 95%CI (0.95, 1.29), P<0.00001]; While for therapeutic purpose, the incidence of overall leukocyte suppression was [RR=0.61, 95%CI (0.38, 0.95), P=0.03], and the white blood cell count was [MD=1.20, 95%CI (0.77, 1.62), P<0.00001]. More importantly, the addition use of Diyushengbai tablet can reduce the application amount of G-CSF. The results showed that the application of G-CSF can be reduced by an average of 1.57 from the beginning of treatment to return normal of white blood cells and around 2.23 in two cycles of chemotherapy. Conclusions: Diyushengbai tablet is more effective in treating leukopenia caused by radiotherapy and chemotherapy than other oral WBC elevating drugs, which has a high clinical value.